Pengurbanan Murid Kristus dalam Perintisan Jemaat Urban Berdasarkan Yohanes 15:13 - Joko Susilo (STT Saint Paul Bandung, 2025)
Abstract The sacrifice of Christ in John 15:13, “Greater love has no one than this: to lay down one’s life for one’s friends,” serves as a profound example for God’s servants who pioneer congregations in urban areas. This study aims to explore the theological meaning of the verse within the context of urban ministry using a descriptive qualitative method with a theological approach. Primary data were collected through interviews and field observations with urban church planters, while secondary data were gathered through literature studies related to biblical theology and urban mission. Through qualitative analysis, the study reveals that pioneering urban congregations demands self-sacrifice, perseverance, and a willingness to face challenges for the sake of the Gospel. Just as Christ gave Himself sacrificially, God’s servants are also called to love and serve urban communities wholeheartedly. These findings not only deepen theological understanding of sacrifice in ministry but also offer spiritual encouragement for church planters to remain faithful and steadfast in their calling.